Content-based instruction strategies applied to comics to reinforce writing skills of third bgu students at “Unidad Educativa Abelardo Moncayo” during 2022-2023 - Morales Jijón, Byron Vinicio (2023)
To propose a guide with Contend-Based Instruction strategies applied in comics for the reinforcement of writing skills in 3rd BGU students at Unidad Educativa Abelardo Moncayo.